1996
DOI: 10.1016/0014-5793(96)00876-9
|View full text |Cite
|
Sign up to set email alerts
|

A possible tyrosine phosphorylation of phytochrome

Abstract: Red/far-red light signal transduetion by the phytochrome family of photoreceptors regulates plant growth and development. We investigated the possibility that tyrosine kinases and/or phosphatases are involved in phytochromemediated signal transduction using crude extracts of oat seedlings that are grown in the dark. We found that a 124 kDa protein was tyrosine-phosphorylated as determined by Western blotting with a phosphotyrosine-specific monoclonal antibody. The 124 kDa protein was recognized by the anti-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A few early studies implicated phosphotyrosines in pathogen and light response, and developmental pathways (Barizza et al, 1999; Kameyama et al, 2000; Sommer et al, 1996; Suzuki and Shinshi, 1995; Tong et al, 1996), but follow-up studies have been lacking. In addition to the early reports, a proteomics study identified a large-scale phosphorylation map in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…A few early studies implicated phosphotyrosines in pathogen and light response, and developmental pathways (Barizza et al, 1999; Kameyama et al, 2000; Sommer et al, 1996; Suzuki and Shinshi, 1995; Tong et al, 1996), but follow-up studies have been lacking. In addition to the early reports, a proteomics study identified a large-scale phosphorylation map in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Autophosphorylation of cyanobacterial phytochrome was promoted by continuous FR irradiation (when Pr should predominate) rather than by continuous R irradiation (when Pfr should predominate) (Yeh et al, 1997). In oat phytochrome, Pfr (Sommer et al, 1996) and also Pr (Yeh and Lagarias, 1998) were phosphorylated. The phytochrome action model (Yeh and Lagarias, 1998) based upon those molecular data is consistent with the idea from the present physiological study that photoconversion of PhyA into Pr by FR light perception promotes a biologically active signal.…”
Section: Photoconversion Of Phya From Pfr To Pr Induces Fr Light-medimentioning
confidence: 95%
“…In particular, the level of tyrosine phosphorylation is determined by the balanced activity of protein tyrosine kinases (PTKs) and PTPs. Moreover, previous study showed that tyrosine phosphorylation is involved in phytohormone responses [16]. Compared with plants, other genomes which lack tyrosine kinases also have very few PTPs.…”
Section: Introductionmentioning
confidence: 99%